Evil Prevention Requirements and the God of Theism - Wood, Adam Noel (Religions, 2022)
The central argument of James Sterba’s “Is a Good God Logically Possible?” relies crucially on the notion that a good God would have to abide by various evil prevention requirements. Because it appears that God has not done so, Sterba concludes that God does not exist. I challenge the notion that theists must accept the notion that God is bound by the particular set of evil prevention requirements Sterba’s argument presupposes. However, I argue that investigating ways God may in fact be required to prevent evils may serve as a helpful heuristic for theists as they seek further to understand God’s nature and purposes.